Exploitation of the Nutraceutical Potential of the Infesting Seaweed Chaetomorpha linum as a Yellow Mealworms’ Feed: Focus on Nutrients and Antioxidant Activity - Annalaura Brai; Edoardo Brogi; Franca Tarchi; Federica Poggialini; Chiara Vagaggini; Sauro Simoni; Valeria Francardi; Elena Dreassi (Foods)
According to the Sustainable Blue Economy Communication, the Farm to Fork Strategy, and the European Green Deal, novel business models supporting the use of resources from oceans and seas are of primary importance. Interestingly, several infesting seaweeds are consumed as foods in Asia and are fundamental ingredients in several traditional dishes. Herein, according to the circular economy approach, we investigate the use of Chaetomorpha linum (CL) as a Tenebrio molitor larvae feed in different percentages: 20%, 50%, and 100%, respectively. We analyzed the effects of CL on the survival and biometric parameters of larvae. The survival rate remained comparable to the control, while the mean weight was inversely proportional to the CL%. The nutrient composition was substantially different from the control, showing increased protein and reduced fat content. Analysis of the secondary metabolites revealed a better fatty acid composition, rich in PUFA, with lipid nutritional indexes comparable to seaweeds and crabs. The simulated gastrointestinal digestion highlights the increased content of essential amino acids, and a two times higher antioxidant activity with respect to the control. Taken together, our results confirm that CL can be used as a TML supplement, with beneficial effects in protein content and fat quality.